Non-redundancy in seed dispersal and germination by native and introduced frugivorous birds: implications of invasive bird impact on native plant communities - Martin Albarracin, Valeria Leticia (2018)
Seed dispersal by vertebrate animals is important for the establishment of many fleshy-fruited plant species. Different frugivorous species can provide different seed dispersal services according to their specific dietary preferences as well as behaviour and body traits (e.g. body size and beak size of birds). Our aim was to study redundancies and complementarities in seed dispersal and germination between the two main native seed disperser birds and the introduced silver pheasant Lophura nycthemera in the temperate Patagonian forests. For this, we collected fresh droppings from the studied species and analyzed seed content. We conducted germination trials for four plant species common in bird droppings; two native species (Aristotelia chilensis and Rhaphithamnus spinosus) and two invasive non-native species (Rubus ulmifolius and Rosa rubiginosa). Both native frugivorous birds and the silver pheasant dispersed fruits of non- native fleshy-fruited plants, but their roles were non-redundant in terms of species dispersed and effect on seed germination. The silver pheasant dispersed a proportionally high number of non-native seeds, while native birds dispersed a high number of native seeds. In addition, the effect of gut treatment in seed germination differed between seed dispersers. Native birds promoted the germination for the two native plant species studied, while the silver pheasant promoted the germination of one non-native plant. This suggests that seed dispersal by the silver pheasant may contribute to the spread of some invasive fleshy-fruited plants in the ecosystems that otherwise would not be dispersed by any other bird. The understanding of redundancies and complementarities on seed dispersal and germination between native and introduced birds will allow improving the management of fleshy-fruited non-native plants.